Improving Higher-Order Thinking Skills-based Science Literacy Questions in Science Learning Using Reading to Learn Model - Lahagu, Aperius; Harefa, Agnes Renostini; Zega, Novelina Andriani; Gulo, Hardikupatu (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Science literacy is important for everyone to have a greater opportunity to adapt in life, especially in terms of mastering reading skills to improve a country's development. The aim of this study was to describe the improvement of science literacy using HOTS questions by applying the R2L model to science learning materials. This research is a quasi-experimental research with one group pretest-posttest design conducted in SMP Negeri 1 Mandrehe Utara. The results of this study showed that there was an increase from the average score of 68.48 (sufficient category) to 83.75 (very good category) and obtained an N-Gain value of 0.42 on moderate criteria. Science competence in explaining phenomena scientifically increased by 16.02, the competence of evaluating and designing scientific investigations increased by 13.54, and the competence of interpreting data and evidence scientifically increased by 16.67 and this competency is the competency that has the highest increase. The application of the R2L model using HOTS questions has given teachers the flexibility to adjust reading materials based on the abilities of students and the situation of science learning so that the improvement of science literacy can be realized.